GE_GERICHTE C/21178/2013 vom 2. Juli 2015 - GE Cour de justice (2015)
PRINCIPE DE LA CONFIANCE(INTERPRÉTATION DU CONTRAT); FORME ORALE; VACANCES; PRESCRIPTION; ABUS DE DROIT | CPC.317; CO.322a.1; CO.329a.1; CO.329d.1; CO.361.1